1986
DOI: 10.1073/pnas.83.19.7518
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin selectively enhances acetylcholine-induced excitations in rat hippocampus and cortex.

Abstract: The neuronal effects of somatostatin-14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Two previous in vivo studies also reported that SST decreases neuronal activity in the rabbit lateral vestibular nucleus (ChanPalay et al, 1982) and in the rat cortex and hippocampus (Mancillas et al, 1986). Noteworthy, these two latter regions express high levels of sst 2A receptors (Dournaud et al, 1996;Schindler et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two previous in vivo studies also reported that SST decreases neuronal activity in the rabbit lateral vestibular nucleus (ChanPalay et al, 1982) and in the rat cortex and hippocampus (Mancillas et al, 1986). Noteworthy, these two latter regions express high levels of sst 2A receptors (Dournaud et al, 1996;Schindler et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…In agreement with this hypothesis, we observed that the reduction of firing level was sometimes accompanied by an increase in action potential size evocative of hyperpolarization. As observed in hippocampus, cortex (Mancillas et al, 1986), and hypothalamus (Peineau et al, 2003), the activation of sst 2A receptors might also lower the discharge rate of MS-DB GABAergic neurons by reducing the postsynaptic excitatory effects of glutamate. This effect might have important functional consequences, because NMDA receptors in the MS-DB are likely to modulate the amplitude of hippocampal theta (Leung and Shen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical and in situ hybridization analysis of this region has shown that the majority of somatostatin-containing neurons are present in the outer part of stratum oriens and in the polymorphic region of the hilus of the dentate gyrus (Johansson et al, 1984;Kiyama and Emson, 1990). Electrophysiological studies have shown a direct inhibitory action of somatostatin on the spontaneous activity of CA 1-CA3 pyramidal neurons (Olpe et al, 1980;Pittman and Siggins, 198 1 ) and a facilitation of the excitatory responses induced by acetylcholine on the same cells (Mancillas et al, 1986).…”
mentioning
confidence: 99%
“…It should be kept in mind that there is a close neuronal interaction between the somatostatinergic and cholinergic systems in the mammalian hippocampus and cortex, as indicated by a number of electrophysiological (Mancillas et al, 1986;Matsuoka et al, 1991), neurochemical (Araujo et al, 1990;Barrios et al, 1990;Gaykema et al, 1991;Zee et al, 1991;Álvaro and Arilla, 1992) and behavioral studies (Haroutunian et al, 1989;Ohno et al, 1993). In the rat hippocampus, cholinergic terminals make synaptic contacts on SS-immunoreactive cells (Leranth and Frotscher, 1987).…”
Section: Discussionmentioning
confidence: 99%